Breathing life into engineering: A lesson study life science lesson. (1st October 2016) - Lawrence, Maria; Yang, Li-Ling; Briggs, May; Hession, Alicia; Koussa, Anita; Wagoner, Lisa
ABSTRACT: A fifth grade life science lesson was implemented through a lesson study approach in two fifth grade classrooms. The research lesson was designed by a team of four elementary school teachers with the goal of emphasizing engineering practices consistent with the Next Generation Science Standards (NGSS) (Achieve Inc.2013 ). The fifth grade teachers challenged and encouraged students to build a mechanical model of a working lung after a previous lesson in which the students learned about the human respiratory system. Teachers' goals to improve students' communication skills and ability to collaborate were also successfully addressed by the research lesson.